Optical Transitions and Charge-Exchange in Highly Charged Quasi-Molecules. (23rd August 2009) - Devdariani, A.; Dalimier, E.; Sauvan, P.
Abstract : The interaction between quasimolecular states produces not only nonadiabatic transitions but also some exotic features in the wings of the spectral profiles emitted by the ions in collision. Although this concept has been fruitfully used for neutral species, some new highlighted experimental data on quasimolecular optical transitions in hot dense plasma have renewed the interest to the concept in the recent years. The present review deals with highly charged quasimolecules and it is dedicated specifically to quasimolecules formed by two bare nuclei and one bound electron. The reason for this choice is that, for such quasimolecules, the energy terms and the dipole moments of the optical transitions can be obtained straightforwardly in nonrelativistic case without any approximation that are typical for neutrals. Although the results obtained in the frame of the approach developed here are directly applicable to the case of single collisions or to low-density plasmas, they form a reasonable initial approximation for the problem of optical profiles in hot dense plasmas and can be regarded as a safe framework for qualitative discussions of profiles in those environments.